A VALUE ADDED ANALYSIS AND DEVELOPMENT STRATEGY OF CHOCOLATE TEMPE COMPANY IN MALANG CITY - IRWANDI, PUTRA - (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2022)
Business development strategy is very important in supporting the sustainability of existing businesses. One of the application development strategies carried out in the chocolate tempe business in Malang City. This study uses a quantitative approach with analytical techniques, namely the IFE matrix, EFE, SWOT matrix and QSPM. The research took place at the De Tempe Chocolate Company, Malang City. The results obtained by the strategy that can be carried out by the Tempe De Konco Chocolate Company are as follows. The SO strategy at the Tempe De Konco Chocolate Company can be done by adding machines to be able to utilize tempe as a high selling power. In the WO strategy, the Tempe De Konco Chocolate Company can do promotions or marketing through social media so that more visitors will visit the Tempe De Konco Chocolate Company. As for the ST strategy, the Tempe De Konco Chocolate Company can do it by adding product differentiation to make it more varied. For the WT strategy, it can be done by adding cooperation partners.